1998
DOI: 10.1159/000020854
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Fetal Nucleated Red Blood Cells from the Maternal Circulation for Prenatal Diagnosis: Experiences with Triple Density Gradient and MACS Based on More than 600 Cases

Abstract: Objective: We wanted to obtain statistically relevant data about the efficiency of our method for the isolation of fetal nucleated red blood cells (NRBCs) from the maternal circulation. Methods: More than 600 samples were investigated using a triple density gradient followed by magnetic separation of anti-CD71-labeled cells, and yields and purities of recovered NRBCs were determined. Results: The enrichment effectivity as well as the morphological condition of cells was reproducibly good, if blood samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…This was largely due to the abundance of erythroblasts in the fetal circulation, scarcity in adult blood, and suitable markers for their enrichment and po-tential identifi cation of fetal erythroblasts [9,10] . During our investigations we observed that both fetal and maternal erythroblasts were present in the circulation of pregnant women, and that the level of both of these erythroblast pools was elevated in preeclampsia [3,11] . Furthermore, a signifi cant correlation was found to occur between circulatory fetal and maternal erythroblasts, suggesting that maternal erythropoiesis was enhanced in preeclampsia.…”
Section: Introductionmentioning
confidence: 60%
“…This was largely due to the abundance of erythroblasts in the fetal circulation, scarcity in adult blood, and suitable markers for their enrichment and po-tential identifi cation of fetal erythroblasts [9,10] . During our investigations we observed that both fetal and maternal erythroblasts were present in the circulation of pregnant women, and that the level of both of these erythroblast pools was elevated in preeclampsia [3,11] . Furthermore, a signifi cant correlation was found to occur between circulatory fetal and maternal erythroblasts, suggesting that maternal erythropoiesis was enhanced in preeclampsia.…”
Section: Introductionmentioning
confidence: 60%
“…Magnetic activated cell sorting (MACS; Miltenyi Biotec, Inc., Sunnyvale, Calif., USA) was performed first by negative selection for the removal of maternal lymphocytes, using anti-CD45 (Serotec Ltd, Kidlington, UK), followed by positive selection for NRBCs with anti-CD71 (Serotec) [12,13].…”
Section: Methodsmentioning
confidence: 99%
“…The CD45− or CD14− cells can then be labeled with a fetal cell marker to target fetal cells within the population. Using a triple density gradient with anti-CD71-labeled cells, Gänshirt et al (1998) showed that the frequency of fetal NRBCs increases with gestational age with yields ranging from 100 to 1000 cells per 40 mL of maternal blood from week 6 of gestation to term.…”
Section: Techniques For Isolating Fetal Cells For Use In Specialized mentioning
confidence: 99%